The Principal’s Academic Supervision on Improving Teachers’ Performance and Students’ Learning Achievement - Sari, Refiana Novita (PPSDP International Journal of Education, 2025)
This study analyzes the influence of principal academic supervision on improving teachers’ performance and student learning achievement. The results of the study indicate that principals, teachers, and employees in secondary schools have implemented academic supervision through classroom observation, feedback, and training. However, there are still some problems faced, such as the lack of sufficient time for intensive supervision and the lack of teacher involvement in the supervision process, as well as the lack of training for employees and the still incomplete facilities. The main focus of this study is to provide a comprehensive explanation of how academic supervision is implemented locally in secondary schools. Thus, the conclusion of this study emphasizes the need for good management in order to improve teachers’ performance and motivate teachers to work better. It is hoped that this study will provide information to schools on how academic supervision can work better than before. This study is expected to be a reference for other researchers to conduct similar research and assist schools in improving the effectiveness of academic supervision.